François Ier et la vie littéraire de son temps (1515-1547) - Rouget, François 1965- (Rencontres, 2017)
This volume describes the official and private image of Francis I of France, analyzes his relationship with the court, and examines specific aspects of the intellectual output produced during his time on the throne. It recalls the major changes that occurred in Europe and reevaluates the king’s influence over political, religious, and literary life.